Development of anaerobic fitness in top-level competitive youth ice hockey players - Leiter, J. R.; Cordingley, D. M.; MacDonald, P. B. (The Journal of Strength and Conditioning Research, 2018)
Ice hockey is a physiologically complex sport involving both the anaerobic and aerobic energy systems. The purpose of this study was to evaluate the anaerobic power output (PO) of top-level competitive youth hockey players. It was hypothesized that with each successive increase in age, there would be an associated change in anaerobic PO. Two hundred and fifty-one male hockey players between the ages of 13-17 years participated in this study. All athletes completed a 30-second Wingate test as part of a preseason physiological and fitness combine. A 1-way analysis of variance was performed to compare peak PO (POpeak), average PO (POavg), and fatigue index between all age groups. A Tukey's post hoc test was used to determine changes in immediately successive age groups for all variables. Age categories were grouped as 13 years old (yrs) (n = 72), 14 yrs (n = 68), 15 yrs (57) and 16 yrs (n = 54, including 11 athletes 17 yrs). Absolute POpeak significantly increased with all age increases. Relative POpeak, absolute POavg, and relative POavg increased between the ages of 13 and 14 years, and 14 and 15 years, but not between the ages 15 and 16 years. There were no changes in fatigue index between any successive age groups. Anaerobic PO increases with an increase in age with no associated change in fatigue index. Athletes, coaches, and parents can use this normative data to help prepare the player for upcoming seasons in which there may be an increase in level or age class.